A diagnostic GDGT signature for the impact of hydrothermal activity on surface deposits at the Southwest Indian Ridge. (September 2016) - Pan, Anyang; Yang, Qunhui; Zhou, Huaiyang; Ji, Fuwu; Wang, Hu; Pancost, Richard D.
Highlights: Tetraether lipid distributions are different among the three deposit types at SWIR. GMGTs occurring in metalliferous sediments are absent in background sediments. GMGTs and high abundance of br GDGTs present in low-temperature hydrothermal deposits. Different hydrothermal activity has diverse impact on tetraether lipid distributions. Abstract: The impact of hydrothermal activity on wider ocean geochemistry and microbial ecology remains a topic of much interest. To explore whether hydrothermal microbial signatures are exported to surrounding marine sediments or if such organisms serve as an important source of sedimentary organic matter, we determined the distributions of glycerol dialkyl glycerol tetraether (GDGT) membrane lipids in surficial normal marine sediments, metalliferous sediments and low-temperature hydrothermal deposits at newly discovered hydrothermal fields and adjacent areas at the Southwest Indian Ridge (SWIR). The GDGTs in those samples varied significantly, evidently representing a variable influence of the hydrothermal activity. GDGT compositions of surficial background sediments in SWIR were similar to those commonly observed in marine sediments, dominated by GDGTs associated with marine planktonic archaea and especially GDGT−0 and crenarchaeol. In contrast, the GDGTs of metalliferous sediments strongly impacted by hydrothermal activity and low-temperature hydrothermal deposits were markedly different, characterized by high relative abundances of isoprenoid GDGTs ( i GDGTs) bearing multiple rings (yielding a higher ring index), low relative abundances of crenarchaeol, and the presence of glycerol monoalkyl glycerol tetraether lipids (GMGTs; so called 'H-tetraethers') that were absent in the normal marine sediments. Sources for these hydrothermal-specific tetraether lipids likely include methanogens and anaerobic methanotrophic archaea (GDGT−0 and GDGT−1–3, respectively), Thermoprotei and Thermoplasmatales (elevated GDGT−3 and 4), and other thermophilic archaea including Methanobacteriales (GMGTs). Deposits influenced by low-temperature hydrothermal activity also contained higher abundances of branched GDGTs ( br GDGTs) typically attributed to soil bacteria. The more distal metalliferous sediments influenced by the neutrally buoyant plume did not contain putative hydrothermal GDGTs, having the same GDGT distribution as the background sediments. This suggests that the neutrally buoyant plume has a limited potential to directly influence the organic matter inputs to surrounding sediments, due to a rapidly waning chemosynthetic microbial contribution relative to normal marine contributions as the plume dispersed and was diluted.